Estimating inter-annual diversity of seasonal agricultural area using multi-temporal resourcesat data. (15th September 2015) - Sreenivas, K.; Sekhar, N. Seshadri; Saxena, Manoj; Paliwal, R.; Pathak, S.; Porwal, M.C.; Fyzee, M.A.; Rao, S.V.C. Kameswara; Wadodkar, M.; Anasuya, T.; Murthy, M.S.R.; Ravisankar, T.; et al.
Abstract: The present study aims at analysis of spatial and temporal variability in agricultural land cover during 2005–6 and 2011–12 from an ongoing program of annual land use mapping using multidate Advanced Wide Field Sensor (AWiFS) data aboard Resourcesat-1 and 2. About 640–690 multi-temporal AWiFS quadrant data products per year (depending on cloud cover) were co-registered and radiometrically normalized to prepare state (administrative unit) mosaics. An 18-fold classification was adopted in this project. Rule-based techniques along with maximum-likelihood algorithm were employed to deriving land cover information as well as changes within agricultural land cover classes. The agricultural land cover classes include – kharif (June–October), rabi (November–April), zaid (April–June), area sown more than once, fallow lands and plantation crops. Mean kappa accuracy of these estimates varied from 0.87 to 0.96 for various classes. Standard error of estimate has been computed for each class annually and the area estimates were corrected using standard error of estimate. The corrected estimates range between 99 and 116 Mha for kharif and 77–91 Mha for rabi. The kharif, rabi and net sown area were aggregated at 10 km × 10 km grid on annual basis for entire India and CV was computed at each grid cell using temporal spatially-aggregated area as input. This spatial variability of agricultural land cover classes was analyzed across meteorological zones, irrigated command areas and administrative boundaries. The results indicate that out of various states/meteorological zones, Punjab was consistently cropped during kharif as well as rabi seasons. Out of all irrigated commands, Tawa irrigated command was consistently cropped during rabi season.